How to unify restrictive and conditional if-clauses - Huitink, Janneke (Proceedings of the Amsterdam Colloquium, 2007)
This paper compares two unifying analyses of restrictive and conditional if-clauses. The first, going back to Lewis and Kratzer, denies that if has any meaning, and attributes seemingly conditional uses to covert operators. The second analysis is due to Belnap and assigns a partial semantics to conditionals. On this account, the difference between restrictive and conditional if-clauses reduces to a mundane scope ambiguity. I will present three reasons to prefer Belnap's analysis.